The Autopoiesis of Architecture : a New Framework for Architecture. (Wiley, 2011)
Take a theoretical approach to architecture with The Autopoiesis of Architecture, which presents the topic as a discipline with its own unique logic. Architecture's conception of itself is addressed as well as its development within wider contemporary society. Author Patrik Schumacher offers innovative treatment that enriches architectural theory with a coordinated arsenal of concepts facilitating both detailed analysis and insightful comparisons with other domains, such as art, science and politics. He explores how the various modes of communication comprising architecture depend upon each other, combine, and form a unique subsystem of society that co-evolves with other important autopoietic subsystems like art, science, politics and the economy. The first of two volumes that together present a comprehensive account of architecture's autopoiesis, this book elaborates the theory of architecture?s autopoeisis in 8 parts, 50 sections and 200 chapters. Each of the 50 sections poses a thesis drawing a central message from the insights articulated within the respective section. The 200 chapters are gathering and sorting the accumulated intelligence of the discipline according to the new conceptual framework adopted, in order to catalyze and elaborate the new formulations and insights that are then encapsulated in the theses. However, while the theoretical work in the text of the chapters relies on the rigorous build up of a new theoretical language, the theses are written in ordinary language? with the theoretical concepts placed in brackets. The full list of the 50 theses affords a convenient summary printed as appendix at the end of the book. The second volume completes the analysis of the discourse and further proposes a new agenda for contemporary architecture in response to the challenges and opportunities that confront architectural design within the context of current societal and technological developments.